2014
DOI: 10.1158/0008-5472.can-13-1934
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Therapeutic Efficacy of a Novel Pharmacologic Inducer of Apoptosis in Malignant Peripheral Nerve Sheath Tumors

Abstract: Neurofibromatosis Type 1 (NF1) is an autosomal disorder that affects neural crest-derived tissues, leading to a wide spectrum of clinical presentations. Patients commonly present with plexiform neurofibromas, benign but debilitating growths that can transform into malignant peripheral nerve sheath tumors (MPNSTs), a main cause of mortality. Currently, surgery is the primary course of treatment for MPNST, but with the limitation that these tumors are highly invasive. Radiation therapy is another treatment optio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 47 publications
(57 reference statements)
2
31
0
Order By: Relevance
“…Bioluminescent imaging was performed as described previously (Chau et al, 2014). Briefly, mice were injected with 160 uL 20 mg/mL D-Luciferin Potassium Salt (Perkin Elmer) in 0.9% sterile NaCl, and total flux was quantified using IVIS Lumina II (Caliper Life Sciences) weekly.…”
Section: Methodsmentioning
confidence: 99%
“…Bioluminescent imaging was performed as described previously (Chau et al, 2014). Briefly, mice were injected with 160 uL 20 mg/mL D-Luciferin Potassium Salt (Perkin Elmer) in 0.9% sterile NaCl, and total flux was quantified using IVIS Lumina II (Caliper Life Sciences) weekly.…”
Section: Methodsmentioning
confidence: 99%
“…Screening a library of 200,000 small molecules on mouse Nf1 -mutant MPNST cells identified compound 21, with selectivity towards NF1 -mutant cells and efficacy in xenografts 173 . Another library-screening study identified UC1 as a small molecule that targets NF1 −/− versus sporadic MPNST cell lines.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…PRC2 loss led to increased levels of acetylated histone H3 of lysine 27 (H3K27Ac), which recruits bromodomain proteins [14]. MPNST cell lines were shown to be sensitive to bromodomain inhibitors [12, 15]. …”
Section: Introductionmentioning
confidence: 99%